Model Pembelajaran Problem Based Learning Berbasis Etnomatematika untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika - I Wayan Widana; Putu Anik Diartiani (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
This study is a classroom action research. The subjects of this study were 42 students of class VII-A in the even semester of SMP Negeri 12 Denpasar in the 2019/2020 school year. The object of research is the activity and mathematics learning outcomes. Student activity data were collected using observation instruments and mathematics learning outcomes were collected using tests. The data were analyzed using qualitative descriptive analysis method. This action research is said to be successful if the students' learning activities are at least in the active category, the average score of mathematics learning outcomes is at least 75, and classical learning completeness is at least 85%. The results showed that there was an increase in the learning activities of students from being quite active in cycle I to being active in cycle II. Meanwhile, the average value of mathematics learning outcomes from 73.66 in the first cycle increased to 80.04 in the second cycle, and there was an increase in students' learning outcomes from 61.90% in the first cycle to 88.09% in the second cycle. Conclusions, the application of the problem based learning model based on ethnomatematics is able to increase the activity and mathematics learning outcomes.